Cultivating Critical Thinking Skills: A Pedagogical Study in a Business Statistics Course - Jessica Bates; Sherri Cheng; Mark Ferris; Xu (Frank) Wang (Journal of Statistics and Data Science Education)
While society expects college graduates to possess critical thinking skills to discern distorted truth, overcome ignorance, and ground action in social reality, recent studies show that traditional lecture-based collegiate instruction may not always support these outcomes. Given that critical thinking skills are essential for college students, who represent society’s future leaders and workforce, it is imperative for higher education to offer effective and comprehensive training to foster these skills. We develop a multi-faceted pedagogical design—Integrated Cogency Method (ICM)—and apply it to a statistics class. Our ICM includes writing assignments that use statistics as evidence, group discussions, and instructor-led Socratic dialogue. We implement a quasi-experimental design to uncover the impact of ICM on improving the students’ critical thinking skills. We objectively assess students’ progress in critical thinking skills by evaluating their written arguments in assignments. Specifically, we measure four critical thinking dimensions: present evidence, explain issues, articulate influence, and present conclusion. The findings from studying 63 students’ essays demonstrate that the implementation of ICM enhances students’ critical thinking skills across all four measured dimensions. We encourage instructors from various disciplines to use the ICM as a reference and create course-specific materials to enhance their students’ critical thinking skills. Supplementary materials for this article are available online.